On a measurement-free quantum lambda calculus with classical control - LAGO, UGO DAL; MASINI, ANDREA; ZORZI, MARGHERITA (Mathematical structures in computer science, 2009)
We study a measurement-free, untyped λ-calculus with quantum data and classical control. This work arises from previous proposals by Selinger and Valiron, and Van Tonder. We focus on operational and expressiveness issues, rather than (denotational) semantics. We prove subject reduction and confluence, and a standardisation theorem. Moreover, we prove the computational equivalence of the proposed calculus with a suitable class of quantum circuit families.